THE INFLUENCE OF ASSET TURNOVER AND SOLVABILITY ON THE PROFIT GROWTH OF FOOD AND BEVERAGES COMPANIES ON THE INDONESIA STOCK EXCHANGE (BEI) FROM 2017 TO 2022 - Idriyansyah Purba, Asra; Lainatusshifa Kemal (JURNAL KREASI RAKYAT, 2023)
This research aims to determine the effect of asset turnover and solvency on profit growth in food and beverage manufacturing companies listed on the Indonesia Stock Exchange 2017-2022. With the quantitative method, it is carried out partially and simultaneously. Simultaneously, asset turnover has a positive and significant effect on profit growth in food and beverage companies listed on the Indonesia Stock Exchange. Partially, solvency has a significant negative effect on profit growth in food and beverage companies listed on the Indonesia Stock Exchange. Based on research conducted, asset turnover and solvency simultaneously have a significant effect on profit growth in food and beverage companies listed on the Indonesia Stock Exchange.